1927 Fla. Laws 212, § 19, pt. 15 (Vol. 2) - (:unkn) unknown (My University, 1927)
Granted the city council the authority to prohibit and regulate the sale of firearms, cartridges, gun shells, or other ammunition for firearms
Keywords: TRANSFER